2017
DOI: 10.1302/2058-5241.2.160076
|View full text |Cite
|
Sign up to set email alerts
|

Acromion and glenoid shape: Why are they important predictive factors for the future of our shoulders?

Abstract: The shape of the acromion differs between patients with degenerative rotator cuff tears and individuals without rotator cuff pathology.It can be assessed in the sagittal plane (acromion type, acromion slope) and in the coronal plane (lateral acromion angle, acromion index, critical shoulder angle).The inter-observer reliability is better for the measurements in the coronal plane.A large lateral extension (high acromion index or high critical shoulder angle) and a lateral down-sloping of the acromion (low later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 44 publications
3
37
0
1
Order By: Relevance
“…It is therefore logical that the supraspinatus tendon rather than the greater tuberosity impinges against the undersurface of the acromion or the coracoacromial ligament. This pathomechanism is consistent with the literature concerning impingement syndrome [ 19 21 ]. CT scans with three-dimensional reconstruction of the shoulder and animation of the bones would therefore not correctly simulate subacromial impingement.…”
Section: Discussionsupporting
confidence: 92%
“…It is therefore logical that the supraspinatus tendon rather than the greater tuberosity impinges against the undersurface of the acromion or the coracoacromial ligament. This pathomechanism is consistent with the literature concerning impingement syndrome [ 19 21 ]. CT scans with three-dimensional reconstruction of the shoulder and animation of the bones would therefore not correctly simulate subacromial impingement.…”
Section: Discussionsupporting
confidence: 92%
“…One hypothesis is that increased subacromial pressure alters the microstructure and the flexibility of the tendons. 6 Tendon degeneration alone, however, does not explain all rotator cuff tears. In many cases, a trauma causes the tendon rupture.…”
Section: See Related Article On Page 3304mentioning
confidence: 99%
“…5 It should be noted that both the critical shoulder angle and the acromion index quantify the lateral extension of the acromion with respect to the glenoid plane and that they are not independent variables. 6 Combining them in a single analysis would maybe provide even better evidence. How a large acromion contributes to rotator cuff lesions needs to be clarified.…”
Section: See Related Article On Page 3304mentioning
confidence: 99%
“…Several authors suggested that a lateralized acromion would result in an overloaded supraspinatus resulting in a tear. 11,13 Nyffeler and Meyer 14 proposed that repetitive compression of the posterosuperior cuff by a lateralized acromion results in altered gliding capacity of the tendon fibrils causing local stress concentration, resulting in a tendon tear. Furthermore, if a preoperatively high CSA or AI could result in an RCT, would decreasing it by lateral acromioplasty minimize the chance of recurrence of a postoperative tear?…”
Section: See Related Article On Page 2553mentioning
confidence: 99%